Association of cardiac magnetic resonance‐detected myocardial abnormalities with disease characteristics and brain natriuretic peptide levels in systemic sclerosis without cardiac symptoms. (28th March 2019) - Sugiyama, Kaita; Kobayashi, Hitomi; Kobayashi, Yasuyuki; Yokoe, Isamu; Takei, Masami; Kitamura, Noboru
Abstract: Aim: This study aimed to evaluate the association between myocardial abnormalities and left ventricular (LV) geometry as assessed using cardiac magnetic resonance imaging (CMRI) in systemic sclerosis (SSc) patients without cardiac symptoms. Methods: SSc patients without cardiac symptoms or cardiovascular risk factors underwent contrast CMRI. CMRI were assessed for structural and functional LV parameters and myocardial fibrosis based on myocardial late gadolinium enhancement (LGE). The correlation between brain natriuretic peptide (BNP) levels and LGE status was evaluated. Results: Among 49 patients, 27 (55%) showed LGE positivity. The most common identified LGE pattern was a linear pattern. LGE was not consistent with coronary artery distribution. There was no difference in ejection fraction between those with and without LGE. LV morphological changes were observed in 29% of SSc patients. An abnormal LV structure was detected in 44% and 14% of patients in the LGE+ and LGE− groups, respectively. The BNP levels were higher by 57% in the LGE+ group than in the LGE−group. Receiver operating characteristic analysis showed that BNP levels reliably detected myocardial abnormalities (area under the curve, 0.72; 95% confidence interval 0.58‐0.88). Conclusions: Myocardial abnormalities were common in SSc patients without cardiac symptoms. We suggest that LV morphological changes may have resulted from myocardial abnormalities. BNP may be useful as a screening tool for the detection of myocardial abnormalities in SSc patients.